2011
DOI: 10.24123/jmb.v10i1.170
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Structure and Timeliness of Financial Report

Abstract: The main objectives of this research are to describe the obedience towards the regulation of timeliness financial report submission and to analyze the influence of financial performance and corporate governance structure to timelines of financial report submission. The research questions are tested by running Analysis of Variance (Anova) and two logistic regressions. Timelines (measured by dummy variable, 1 if the company comply financial report submissioni.e. before and at 31 of March, while 0 for delayed sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The timeliness of submissions of financial reporting is considered vital for both external and internal users since it provides useful and updated information allowing them to make the right decisions (Gunarsih 2011;Beest et al 2009). Furthermore, previous literature reveals that the issuing date of annual reports is influenced by corporate governance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The timeliness of submissions of financial reporting is considered vital for both external and internal users since it provides useful and updated information allowing them to make the right decisions (Gunarsih 2011;Beest et al 2009). Furthermore, previous literature reveals that the issuing date of annual reports is influenced by corporate governance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding suggested that members who have financial background contribute to the enhancement of issuing date of annual financial reports. Gunarsih (2011) studied the effect of ownership concentration by the domestic institutions on the timeliness of financial reporting among Indonesian companies listed in the Indonesian stock exchange during the period of 1999-2007. The result of the study shows that there is a positive relationship between corporate governance structure (ownership concentration by domestic institution) and issuing date of annual financial reports.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations